2018
DOI: 10.1007/s13201-018-0750-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZnO nanostructure using activated carbon for photocatalytic degradation of methyl orange from aqueous solutions

Abstract: In this research, zinc oxide (ZnO) nanostructure was prepared by using zinc acetate (as precursor) and carboxylic derivative of activated carbon (as matrix). Activated carbon was modified by oxidation with nitric acid to get carboxylic derivative (AC-COOH). Then, zinc was loaded on the surface of modified activated carbon by an impregnation method. The ZnO nanostructure was characterized by BET, XRD and SEM that confirmed achieving of ZnO nanoparticles with a size of 21-31 nm and surface area of 17.78 m 2 gr −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 46 publications
(46 reference statements)
3
45
0
Order By: Relevance
“…Activated carbon in its bare form supports the growth of bacteria due to its biocompatibility. Activated carbon with antibacterial activity can be produced by impregnation of silver nanoparticles [2][3][4][5][6], or metallic oxides such as ZnO [7]. Furthermore, silver and ZnO nanoparticles supported on activated carbon have gained much attention for adsorption [6,[8][9][10][11][12][13][14][15][16], and catalytic applications [7,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon in its bare form supports the growth of bacteria due to its biocompatibility. Activated carbon with antibacterial activity can be produced by impregnation of silver nanoparticles [2][3][4][5][6], or metallic oxides such as ZnO [7]. Furthermore, silver and ZnO nanoparticles supported on activated carbon have gained much attention for adsorption [6,[8][9][10][11][12][13][14][15][16], and catalytic applications [7,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…5). These results could be related to the calcination procedure in the presence of oxygen atmosphere that occurs by different mechanisms depending of the zinc salt precursor 18,42 . Thus, a two-step process could explain the differences obtained in the morphologies of our composites (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…1115 that generate hydroxyl free radicals as oxidizing agents that decompose the organic contaminants to CO 2 and H 2 O in the presence of UV light, hydrogen peroxide or ozone 2,1517 . Compared to pure inorganic metal oxides, the nanomaterials that use biochar as support for the deposition of the inorganic particles can promote the photodegradation of the organic dyes with increased degradation rate 1820 . Thus, several research studies not only demonstrated higher efficiencies in terms of decomposition of the organic dyes, but also confirmed that the structure, morphology, or the functional groups present on the surface of the biochar are extremely important for the immobilization and/or synthesis of the metal oxides nanoparticles leading to an enhanced photocatalytic degradation process 18,20,21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various forms of carbon, the activated carbons (ACs) have been considered for the immobilization of photocatalytic materials due to their favorable properties such as large surface area, porosity, good adsorptivity, and convenience in handling [ 25 , 26 , 27 ]. The composites of ZnO with ACs have been synthesized in previous studies [ 28 , 29 , 30 ]; however, the high cost of commercial AC limits its application worldwide [ 2 ]. Therefore, there is a growing interest in the economic production of ACs.…”
Section: Introductionmentioning
confidence: 99%